Causas frecuentes para retrasos en proyectos de sistemas de riego: Caso de estudio zonas Andinas de Chimborazo. - Sagñay Anilema, Lucas Adrián (2025)
Ecuador is divided into the Coastal, Highland, and Amazonian regions, with the Highlands standing out as the Andean zone due to its mountainous geography and variable climate, where agriculture is a major economic activity. To guarantee agricultural activity in Andean zones such as Chimborazo, Tungurahua, Cotopaxi, and Bolívar, it is necessary to have efficient irrigation systems as soon as possible. However, their construction faces serious technical and administrative challenges, resulting in delays, cost overruns, and poor-quality work. This study aimed to identify the most frequent causes of these delays, analyze their effects, and propose improvement strategies, applying a mixed-methods approach based on the documentary analysis of 38 irrigation projects completed over the last 10 years and surveys of professionals with experience in irrigation projects in Andean zones. The results showed that the main causes of delays in irrigation projects in Andean zones are concentrated in the early stages of the project life cycle. Therefore, an improvement strategy is proposed, organized by project stages, aligned with the SOCE public procurement system, and integrated with tools such as the project management approach outlined in PMBOK and the BIM methodology.